Epidemiological Aspects Related to the Dental Health of Children Victims of Abuse, Violence and Dental Neglect - Bălan Adriana; Bălan Gheorghe (Romanian Society of Oral Rehabilitation, 2012)
Child abuse and neglect implies a multitude of experiences that are threatening or harmful to the child and are the outcome of commisive or omissive acts on the part of a responsible caretaker. Child maltreatment affects millions of children worldwide and has become a serious epidemiological factor related to the paediatric oral health. Aim The purpose of this study is to identify the regional ampleness of child maltreatment using statistical legal medicine data. Secondarily we intend to ascertain the main risk-factors epidemiologically related to child abuse and to suggest some measures that may meliorate the oral health status connected to child maltreatment. Material and Methods For our analysis we used a group of 591 children that received medico-legal certificates issued by the Institute of Legal Medicine, Iasi, during the 16th of January 2007 and the 30th of September 2008. 54,1% (320) of the group presented oral trauma, 87.5% (280) of whom were victims of abuse and violence. Nevertheless we examined various laws related to this field and tried to discover countermeasures against child maltreatment. Results and Discussion The result was the correlation between all the parameters in the observed group using statistical methods as the Square-Chi test or the Spearman Rank. Furthermore, we tried to analyze the implication of the legal and social background as etiological factors for child abuse. Conclusions Child maltreatment is a frequent reality in the analyzed group. Not only physical abuse, but also sexual, emotional or verbal abuse and neglect are forms of child maltreatment. Domestic violence and negligence are social disorders that have many implications in the pediatric oral health. Nevertheless, there are some points where the penal law should be changed in order to positively affect this situation.